Surpeuplement des logements en lien avec la détresse psychologique chez les adolescents inuit du Nunavik : un suivi longitudinal - Pepin, Camille (Université Laval, 2019)
About half of Nunavik Inuit live in overcrowded households compared to 6% of the general Canadian population. Inuit adolescents are also more at risk of suffering from psychological distress than their Canadian peers. Living in overcrowded households is associated with greater risks of suffering from mental health problems for Canadian adolescents. However, no empirical and longitudinal study has examined the impact of living in an overcrowded household during childhood on psychological distress at adolescence for Inuit. The objective of the present work is to examine the hypothesized relationship between household overcrowding at childhood and psychological distress during adolescence among Nunavik Inuit, as well as the hypothesized relationship between these phenomena when they are both measure at adolescence. It will also examine if this relationship is moderated by sex. Recruited as part of the Nunavik Child Development Study, 220 participants were met when they were 11 years old in average, and then when they were 18 years old in average. Household overcrowding was assessed using the people per room ratio. Psychological distress symptoms were operationalized at adolescence using depressive symptoms and suicidal thoughts. The results did not show that childhood household crowding had a longterm effect on psychological distress, nor effect moderation by sex. Despite these results, household crowding could be a risk factor when in interaction with other elements related housing conditions or with poverty, or could be experienced as a difficulty for adolescents on other aspects than depressive symptoms and suicidal thoughts. Près de la moitié des Inuit du Nunavik vivent dans des logements surpeuplés comparativement à 6 % de la population générale canadienne. Les adolescents inuit sont aussi plus à risque de souffrir de détresse psychologique que leurs pairs canadiens. Habiter un logement surpeuplé est associé avec un risque accru de souffrir de troubles de santé mentale pour les adolescents canadiens. Le ...